A green band in a parched and burning land : Sobaipuri O'odham landscapes - Seymour, Deni J. (University Press of Colorado, 2022)
"A Green Band in a Parched and Burning Land presents a detailed understanding of the Sobaipuri O'odham -- the most influential Indigenous group in southern Arizona in the early historic period. Seymour combines historical sources with archaeological data and oral history to reveal the native history of the region"--